2022
DOI: 10.1039/d2ta07315c
|View full text |Cite
|
Sign up to set email alerts
|

Boosting exciton dissociation and charge separation in pyrene-based linear conjugated polymers for efficient photocatalytic hydrogen production

Abstract: Conjugated organic polymers (COPs) have recently attracted intense interest in photocatalytic hydrogen evolution (PHE) due to their easily tuned properties, high stability, and processability. However, most COPs photocatalysts displayed poor...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
13
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 26 publications
(13 citation statements)
references
References 61 publications
0
13
0
Order By: Relevance
“…We also tried different sacrificial agents including lactic acid (LA), triethylamine (TEA), triethanolamine (TEOA), and Na 2 SO 3 for the photocatalytic measurement of PyT-BTDO-2. The results demonstrated that the HER values of PyT-BTDO-2 in the above cases are lower than those using an AA sacrificial hole scavenger under the identical photocatalytic reaction conditions (Figure S8), which demonstrates that AA is the optimal sacrificial agent for PyT-BTDO-2, as reported for most narrow band gap polymer photocatalysts. Besides, we also carried out the photocatalytic measurement in pure water without using any sacrificial agents. However, no any hydrogen signal could be detected for PyT-BTDO-2 in pure water.…”
Section: Resultsmentioning
confidence: 53%
“…We also tried different sacrificial agents including lactic acid (LA), triethylamine (TEA), triethanolamine (TEOA), and Na 2 SO 3 for the photocatalytic measurement of PyT-BTDO-2. The results demonstrated that the HER values of PyT-BTDO-2 in the above cases are lower than those using an AA sacrificial hole scavenger under the identical photocatalytic reaction conditions (Figure S8), which demonstrates that AA is the optimal sacrificial agent for PyT-BTDO-2, as reported for most narrow band gap polymer photocatalysts. Besides, we also carried out the photocatalytic measurement in pure water without using any sacrificial agents. However, no any hydrogen signal could be detected for PyT-BTDO-2 in pure water.…”
Section: Resultsmentioning
confidence: 53%
“…The transient decay kinetics of the two samples were fitted by a biexponential function (Figure c,d). Remarkably, polymer ThSo-1 possesses a shorter lifetime (τ 1 = 4.57 ± 0.27 ps) and a longer lifetime (τ 2 = 36.34 ± 2.20 ps), which belong to the nonradiative recombination process and the recombination between the electrons and holes, respectively. , The longer lifetime component of ThSo-1 was larger than that of ThSo-2 (τ 2 = 36.24 ± 3.87 ps), which indicated that the strong electron-deficient acceptor BTDO in ThSo-1 reduced electron/hole recombination and greatly enhanced carrier separation and migration, prefiguring the high activity of ThSo-1 in the PHP activity. , …”
Section: Resultsmentioning
confidence: 93%
“…The short photoluminescence lifetimes of the three polymers indicate a faster electron transfer rate to the surface, which should be favourable for the HER. 28,49,[53][54][55] As shown in Fig. 6b, TPDBDT NPs exhibited the smallest Nyquist radius, indicating that they had the highest quality of the interface among the three TPD-based polymers, which is in favour of charge transport at the NP interface.…”
Section: Photocatalytic Hydrogen Productionmentioning
confidence: 99%
“…16 In this way, the electron-deficient thieno [3,4-c] pyrrole-4,6-dione (TPD) with symmetric coplanar structure is introduced into the backbone as an "A" unit to increase the conjugation and planarity of polymer and enhance interchain π-π stacking through intramolecular noncovalent interactions between the oxygen and the sulfur (or hydrogen) atoms, resulting in high charge carrier mobility and efficient charge transport of the obtained materials. 26 In addition, as revealed by previous studies, the introduction of functional groups with great electronegative atoms, such as OvSvO, 16,18 CvO, 27,28 F, 29 and CN, 30 can modify the surface chemistry and the energy band structure of organic polymer photocatalysts, thus significantly affecting the photocatalytic performance. For example, Lin et al developed a new conjugated small molecule photocatalyst (Y6CO) by introducing one carbonyl group in the fused-ring core as a "claw" to efficiently anchor Pt cocatalyst through σ-π coordination, achieving state-of-the-art HER performance.…”
Section: Introductionmentioning
confidence: 97%